1999
DOI: 10.1172/jci4138
|View full text |Cite
|
Sign up to set email alerts
|

Lung fluid transport in aquaporin-1 and aquaporin-4 knockout mice

Abstract: Substantial quantities of fluid move across epithelial and endothelial barriers in lung. In the perinatal lung, fluid absorption from the airspaces occurs in preparation for alveolar respiration (1). In the adult lung, movement of salt and water between the airspace and capillary compartments is required for control of airspace hydration. The formation and resolution of clinical pulmonary edema involve fluid movements among the airspace, interstitial, and capillary compartments (2-4). Considerable progress has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 222 publications
(174 citation statements)
references
References 39 publications
6
166
1
1
Order By: Relevance
“…Our data concerning the immunoreactivity of the endothelium of CAM blood vessels to AQP1 suggest that also at this level AQP1 might be implicated in governing the water pathway through the endothelium, as has been established in the descending vasa recta (Pallone et al, 2000) and in microvessels of alveolar and distal airways (Bai et al, 1999). Moreover, in AQP1 knockout mice it has been shown that AQP1 provides a quantitatively important "exclusive water pathway" for osmotically induced water movement across the capillary endothelium (Yang et al, 1999), representing 10 -45% of the total transcellular hydraulic permeability of the microvascular wall (Renkin and Curry, 1982;Wolf and Watson, 1989).…”
Section: Resultssupporting
confidence: 55%
“…Our data concerning the immunoreactivity of the endothelium of CAM blood vessels to AQP1 suggest that also at this level AQP1 might be implicated in governing the water pathway through the endothelium, as has been established in the descending vasa recta (Pallone et al, 2000) and in microvessels of alveolar and distal airways (Bai et al, 1999). Moreover, in AQP1 knockout mice it has been shown that AQP1 provides a quantitatively important "exclusive water pathway" for osmotically induced water movement across the capillary endothelium (Yang et al, 1999), representing 10 -45% of the total transcellular hydraulic permeability of the microvascular wall (Renkin and Curry, 1982;Wolf and Watson, 1989).…”
Section: Resultssupporting
confidence: 55%
“…In each of these systems the rate of transepithelial fluid secretion normalized to epithelial surface area is very high, such that the reduced but non-zero water permeability in AQP deficiency impairs transepithelial osmotic equilibration. In other epithelia, where areanormalized rates of fluid absorption/secretion are much lower, AQPs are not required for transepithelial fluid transport, as found for tear fluid secretion by lacrimal gland , sweat secretion (Song et al, 2002), alveolar fluid absorption (Bai et al, 1999;, and airway fluid absorption . Involvement of AQP-in the reduced tear fluid secretion in Sjogren's syndrome has been suggested (Tsubota et al, 2001), though subsequently refuted (Beroukas et al, 2001).…”
Section: Aqp Roles Related To Aqp-facilitated Water Transportmentioning
confidence: 97%
“…Water can travel through transcellular channels known as aquaporins. However, studies using specific aquaporin-null mice have demonstrated that these channels do not have significant roles in alveolar fluid absorption despite their importance in osmotically driven water movement across epithelial and endothelial cell barriers in the lung [10][11][12][13][14][15]. Cl − is secreted into the alveolar space via the cystic fibrosis transmembrane regulator (CFTR) [16]; this receptor also plays a role in cAMP-mediated fluid transport [17,18].…”
Section: Alveolar Fluid Transportmentioning
confidence: 99%